DYNAMICS OF EXCHANGE PARAMETERS OF ULTRASONIC HEART RESEARCH IN PATIENTS WITH CLIMACTERIC SYNDROME ASSOCIATED WITH HYPOTHYROIDISM UNDER THE INFLUENCE OF COMPLEX THERAPY - Павловська, М.О.; Vakaluk, V.P.; Deltsova, E.I. (World of Medicine and Biology, 2018)
The study of the most common diseases, including the endocrine, arising from menopause or existing somatic disorders, is extremely relevant, since the combination of endocrine system diseases and climacteric syndrome creates conditions for mutual obstruction, masking of clinical manifestations of diseases or changes in the course of the main endocrine disease as in itself, and against the background of HRT. Any endocrine dysfunction negatively affects both metabolic processes throughout the body, and on the emotional and personal background of the patient. The presence of diabetes mellitus, obesity, pathology of the thyroid gland or other endocrinopathies in most cases requires an individual approach with the appointment of a comprehensive treatment of climacteric disorders with the aim of their adequate correction. The incidence of cardiovascular disease in the climacteric period is significantly increased, as hormonal deficiency of estrogens is associated with known common risk factors (hypodynamia, smoking, inappropriate nutrition, weight gain, etc.) in women. In addition to mediated action through a cascade of biochemical reactions, estrogens affect the vascular wall. In blood vessels, there are estrogen alpha and beta receptors. The effect of estrogens is through endothelial cells and is to stimulate production of vasodilator (nitric oxide and prostacyclin) and inhibit vasoconstrictive factors (endothelin 1 and thromboxane. It has been shown that the thickness of the arterial walls increases with an increase in the duration of menopause, indicating the effect estrogen on the thickness of the vascular wall. The direct influence of estrogen on the myocardium, which consists in increasing the minute and shock volumes, improvement of the diastolic function, inhibition of remodeling processes in myocardium. Goal: to compare the effectiveness of complex therapy of climacteric syndrome in patients with hypothyroidism by analyzing the parameters of echocardiography before and after complex treatment using physiotherapeutic and antihomotoxicological agents. 101 patients aged 45-55 years with a climacteric syndrome associated with hypothyroidism were examined. Women in group 1 (n = 34) received only base therapy according to the National Consensus on the management of patients in the climacteric period. For group 2 (n = 34), physiotherapy (ultrasound therapy and contrast baths 2 times / week for two months) was applied against base therapy. For group 3 (n = 33), in addition to basic therapy, antigmotoxic drugs were prescribed. Conclusions. In women with hypothyroidism in perimenopause, most of the functional characteristics of the cardiovascular system are different from the norm. The comparison of the effectiveness of therapeutic programs revealed that the proposed complexes to a greater or lesser extent positively influenced the state of the cardiovascular system of patients, and also reduced the severity of the climacteric syndrome (an effect on all components of the climacteric syndrome, but to a greater extent on the psychoemotional component) was observed. At the same time, summarizing the results, it can be concluded that for patients with climacteric syndrome and hypothyroidism, a complex that included antihomotoxicological agents was more effective, as evidenced by the dynamics of echocardiographic parameters. From a clinical point of view, the results provide a reasonable basis for recommending these complexes for the correction of functional cardiovascular disorders in women with climacteric disorders, against the background of thyroid gland hypofunction.